Interpreting qualitative data - Silverman, David (Sage, 2014)
The book offers beginners unrivalled hands-on guidance to help them get the best out of a research methods course or research project. A streamlined structure to aid navigation and guide readers smoothly through the research process. A new chapter on generalizing from case-study research which addresses the perennial issue of ‘how many cases do you need?’ New material on doing qualitative research online and the ethics of internet research. Additional sections covering organizational documents and documents of everyday life, including blogs and diaries. Many more recent case study examples drawn from a broad range of disciplines including business, education, social work and geography as well as health studies. A new and improved companion website, full of additional resources for students and lecturers.